Surrogacy in India: Legality (International Journal of Scientific Research and Management (IJSRM), 2015)
Surrogacy in India is becoming the concern issue these days because in India surrogacy plays an important role for those who does not have the capacity to have her own child. Now a days India becomes the best place known for the surrogacy because of so many reasons and one reason behind this is the legality of surrogacy in the country. In this article I only discuss the about the surrogacy, its types and what is the legality behind surrogacy.